A STUDY ON RELATIONSHIP BETWEEN SOCIO-ECONOMIC STATUS AND AGGRESSION AMONG BALL BADMINTON PLAYERS. - Reddy, A.Sankar (The journal of contemporary issues in business and government, 2009)
The paper is an empirical attempt to explore the significant influence on the aggressive behavior of the Socio Economic Condition. A sample of 100 players in the age group of 19 to 25 years studied by using semi- structured interview schedule. It is explored that the Socio Economic of the players has something to do with the aggressive behavior.